2023
DOI: 10.21037/jtd-23-1277
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative multidisciplinary management and expertise of cT2–3 locally advanced operable esophageal squamous cell carcinoma: a report of two cases

Xuefeng Leng,
Daisuke Kurita,
Yi Zhu
et al.

Abstract: Background The accurate clinical staging of esophageal squamous cell carcinoma (ESCC) is pivotal for guiding treatment strategies. However, the current precision in staging for clinical T (cT)2 and cT3 stages remains unsatisfactory. This article discusses the role of multidisciplinary teams (MDTs) in the clinical staging and formulation of neoadjuvant treatment strategies for locally advanced operable ESCC. These challenges underscore the importance of precise staging in the decision-making proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In the present paper ( 1 ), Leng et al have evaluated the multidisciplinary management of operable clinical T2–3 esophageal squamous cell carcinomas (ESCCs) by presenting two case reports to several experts, within different professions, on three continents: East-Asia (China, Japan, and Korea), America (the Unites States) and Europe (the Netherlands). The authors conclude that further research is needed to address the challenges in clinical staging, as it is found to be very difficult to differentiate between T2 and T3 tumors.…”
mentioning
confidence: 99%
“…In the present paper ( 1 ), Leng et al have evaluated the multidisciplinary management of operable clinical T2–3 esophageal squamous cell carcinomas (ESCCs) by presenting two case reports to several experts, within different professions, on three continents: East-Asia (China, Japan, and Korea), America (the Unites States) and Europe (the Netherlands). The authors conclude that further research is needed to address the challenges in clinical staging, as it is found to be very difficult to differentiate between T2 and T3 tumors.…”
mentioning
confidence: 99%